Stress effects of cyanotoxin β‐methylamino‐L‐alanine (BMAA) on cyanobacterial heterocyst formation and functionality. Issue 3 (6th May 2018) - Popova, Alexandra A.; Rasmussen, Ulla; Semashko, Tatiana A.; Govorun, Vadim M.; Koksharova, Olga A.
Summary: Various species of cyanobacteria, diatoms and dinoflagellates are capable of synthesizing the non‐proteinogenic neurotoxic amino acid β‐N‐methylamino‐L‐alanine (BMAA), which is known to be a causative agent of human neurodegeneration. Similar to most cyanotoxins, the biological and ecological functions of BMAA in cyanobacteria are unknown. In this study, we show for the first time that BMAA, in micromolar amounts, inhibits the formation of heterocysts (specialized nitrogen‐fixing cells) in heterocystous, diazotrophic cyanobacteria [ Anabaena sp. PCC 7120, Nostoc punctiforme PCC 73102 (ATCC 29133), Nostoc sp. strain 8963] under conditions of nitrogen starvation. The inhibitory effect of BMAA is abolished by the addition of glutamate. To understand the genetic reason for the observed phenomenon, we usedqPCR to study the expression of key genes involved in cell differentiation and nitrogen metabolism in the model cyanobacterium Anabaena sp. PCC 7120.We observed that in the presence of BMAA, Anabaena sp. PCC 7120 does not express two essential genes associated with heterocyst differentiation, namely, hetR and hepA . We also found that addition of BMAA to cyanobacterial cultures with mature heterocysts inhibits nifH gene expression and nitrogenase activity.